Characterizing T cell responses to enzymatically modified beta cell neo-epitopes - Nguyen, Hai; Arribas-Layton, David; Chow, I-Ting; Speake, Cate; Kwok, William W.; Hessner, Martin J.; Greenbaum, Carla J.; James, Eddie A. (Frontiers in Immunology, 2023)
Previous studies verify the formation of enzymatically modified self-peptides and their preferred recognition by T cells in subjects with type 1 diabetes (T1D). However, questions remain about the relative prevalence of T cells that recognize modified self-peptides derived from different antigens, their functional phenotypes, and whether their presence correlates with a specific disease endotype. To address this question, we recruited a cohort of subjects with T1D who had high or low levels of residual beta cell function. Using previously developed HLA class II tetramer reagents, we directly enumerated T cells that recognize modified GAD65 epitopes in the context of DRB1*04:01 or modified IA-2 epitopes in the context of DQB1*03:02 (DQ8). Consistent with prior studies, we observed higher overall frequencies in subjects with T1D than in HLA matched controls. Notably, DQ8 restricted responses to modified IA-2 were over-represented in subjects with lower residual beta cell function. T cells specific for both groups of epitopes could be expanded from the peripheral blood of subjects with established T1D and at risk subjects. These neo-epitope specific T cells had similar functional profiles in subjects with T1D and primarily produced interferon gamma. Neo-epitope specific T cells in at risk subjects with multiple antibodies produced higher amounts of interferon gamma and lower amounts of IL-4 than at risk subjects with single antibodies, suggesting a shift in polarization during progression. These results reinforce the relevance of modified neo-epitopes in human disease and indicate that responses to distinct neo-antigens accompany a more rapid decline in beta cell function.